Coupled modeling of combustion and hydrodynamics for a coal-fired supercritical boiler. (15th March 2019) - Chen, Tang; Zhang, Yan-jun; Liao, Meng-ran; Wang, Wei-zong
Abstract: Computational fluid dynamics (CFD) model of coal combustion is coupled with the one-dimensional hydrodynamic model of supercritical steam, and applied in the simulation of the superheater. The convective heat exchangers are neglected. Complex tube arrangements can be modeled with the aid of AutoCAD, and therefore the simulation could offer detailed information on heat exchangers. It is found that the outlet steam temperature of the tube is very sensitive to the variation of ash deposit temperature. Therefore it is not reasonable to use decoupled method for predicting the energy flux transported to the steam. The outlet steam temperature of a row of tubes is compared with the running data from the power plant. The simulation result fits well with running data. Nevertheless, one can impose an average steam temperature plus 50 K as the tube outside surface temperature; then calculates the temperature of the ash deposit according to the thermal resistance of ash deposit and energy flux. The result from this "simplified" coupled method is very close to fully coupled method.